Subtitle in Teaching Pronunciation with Video - Roki Ranjani Sanjadireja (Department of English Language Education, UIN Sunan Ampel Surabaya, 2020)
Video has been a tool to improve learning outcome, but many teachers do not apply the correct procedure in using video as the medium of teaching pronunciation. Pronunciation should have taken its fascination into classroom teaching learning. This research’s objective is to test the use of video’s subtitle in teaching pronunciation and its impact to students’ pronunciation. This research is quantitative study with design of true experiment post-test only. One group watches non subtitled video and the other watches subtitled video. The researcher has found that watching video only, with subtitle or no subtitle, does not improve students’ pronunciation. It is suggested that teacher may have to do another activity such as enhancement, repetition or scaling in teaching pronunciation rather than watching only.